Assessment of scenic, natural and cultural heritage for sustainable management of tourist beaches. A case study of Gran Canaria island (Spain). (March 2018) - Peña-Alonso, Carolina; Pérez-Chacón, Emma; Hernández-Calvento, Luis; Ariza, Eduard
Highlights: This research studies beach heritage through an indicator system. Beaches were analyzed as socio-ecological systems with different dimensions. The processes identified have particularities at the different types of beach. Human occupation affects to the relationship among dimensions of heritage. Abstract: In the last few decades, the recreational use of beaches and their surrounding areas has increased substantially, influencing the alteration and the loss of heritage elements. For beaches with year-round tourist activity, such as those located in the Canary Islands (Spain), it is especially important to evaluate heritage-based values and in this way contribute to their preservation and integration in local management policies. In this work, an indicator system (comprised of three partial indices: scenic, natural and cultural value) is developed, integrating scientific-technical procedures with narratives of different stakeholders (users, managers, academics, etc.) to assess the value of heritage-based assets in urban, semi-urban and natural beaches. The results obtained reflect a low cultural value and moderate-high scenic value for the three beach types and a high natural value for urban beaches, which is by contrast low in semi-urban beaches. Special importance is given to the need to integrate the heritage values that were identified in the management and planning of each beach.